Developmental norms as a statistical model of Polish child development versus regional norms of physical development - Kaliszewska-Drozdowska, Maria Danuta (Anthropological Review, 1978)
This paper compares present regional norms of physical development of children and youth. As a reference system cross-country data of The Second Antropometric Survey organized by Anthropometric Committee of Polish Academy of Sciences in 1966 - 68 published by S. Niemiec [Wolański et al. 1975] were employed. Comparisons encompass individuals aged 7 - 18 years.For separate regional norms standarized deviations from „Polish norm” were calculated for body height and weight in examined age groups for both sexes (tab. 1 and 2). Values of standarized deviations lie in the range —.839 to +1.363. Furthermore, average deviations of regional norms from the Polish norm were calculated (fig. 1-4). Results of these calculations point toward the fact that arithmetic means of regional norms lie within X+1 SD range of the „Polish norm”, hence being within the: range commonly accepted as a statistical norm.From the analysis of data it results that there is no considerable diversity between children from various regions of the country. Simultaneously, still observed regional differences gradually disappear as standard of living increases. However, these changes occur faster in large urban agglomerations than in rural settlements. This fact is illustrated on figures 1 through 4: regional norms for rural regions show negative deviations. It is noteworthy that positive deviations are in terms of' absolute numbers twice higher than negative ones.Moreover it has been shown that it is impossible to conclude upon the size of differences in physical development of children from various regions because authors. of regional norms have applied discrepant methods for their data elaboration.In conclusion the author states that for the whole country one and the same norm can be used, It is still open to debate whether this should be „generalizing norm” being average representation of current state of growth over entire population or „aim norm” constructed on grounds of observations of individuals having the best. at present time indices of physical growth in the country.